PENYULUHAN TEKNIK AKUPRESUR DENGAN MEDIA VIDEO EFEKTIF MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN REMAJA PUTRI DALAM PENGURANGAN DISMENOREA - Swandari, Ni Kompiang Ayu; Somayani, Ni Ketut; Ningtyas, Listina Ade Widya (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023DO - 10.24843/ACH.2023.v10.i03.p05, 2023)
ABSTRACT Dysmenorrhoea is a condition that occurs during menstruation and causes disruption of activity and requires treatment. Non-pharmacologically it can be done with acupressure techniques. The purpose of this study was to determine the effectiveness of counseling on the knowledge and skills of adolescent girls about acupressure techniques for reducing dysmenorrhoea in SMP Negeri 4 Tabanan. Type of pre-experimental research design one group pre-post test design. The implementation in April 2023 uses a total sampling technique that meets the inclusion creteria with a total sample of 26 class VIII students. Data were collected using questionnaires and observation sheets analyzed using the Wilcoxon test. The results showed an increase in the knowledge score of young women before and after counseling from 66.15 to 80.51an increase of 13.33% and the skill score of young women before and after counseling from 18.97 to 74.42 an increase of 55%. The results of the bivariate test showed differences in adolescent girls' knowledge (p-value 0.00) and skills (p-value 0.00) about acupressure techniques to reduce dysmenorrhoea. The conclusion is counseling with power point media and effective videos on young women's knowledge and skills about acupressure techniques for dysmenorrhoea reduction. Keywords: Knowledge, Skills, Acupressure, Dysmenorrhoea, Youth